The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1108/ijoa-05-2013-0667
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and gender on decision-making models and leadership styles of non-profit executives in Texas, USA

Abstract: Purpose The purpose of this study is to fill the gap by investigating the relationship between age and other demographics on decision-making and leadership styles of executives in the non-profit sector. Design/methodology/approach This study is a quantitative research using correlation analysis and analysis of variance. The quantitative approach establishes facts, makes predictions and tests stated hypothesis and used the Pearson correlation coefficient, the ANOVA and the two-way analysis of variance. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In addition, cognitive styles are trait-based individual differences that represent how someone perceives and processes information across a broad range of contexts [75], including rational ability and rational engagement, which reflect an individual's ability and preference to think in a logical way [76], and which have also been discussed in terms of experiential ability and experiential engagement, which represent the ability and preference to rely on impressions and feelings [76]. Uzanwanne's [77] study revealed that the education and age of executives significantly influence leadership styles and decision-making models.…”
Section: Previous Research On the Relationship Between Decision-makin...mentioning
confidence: 99%
“…In addition, cognitive styles are trait-based individual differences that represent how someone perceives and processes information across a broad range of contexts [75], including rational ability and rational engagement, which reflect an individual's ability and preference to think in a logical way [76], and which have also been discussed in terms of experiential ability and experiential engagement, which represent the ability and preference to rely on impressions and feelings [76]. Uzanwanne's [77] study revealed that the education and age of executives significantly influence leadership styles and decision-making models.…”
Section: Previous Research On the Relationship Between Decision-makin...mentioning
confidence: 99%
“…The importance of the age of leaders in taking into account the leadership style and the conflict resolution model is highlighted in the research (Uzonwanne, 2016), which shows how leadership patterns are changing, even existing intergenerational collisions.…”
Section: Literature Review Hypothesis Of the Paper 21 Leadership Styl...mentioning
confidence: 99%
“…The decision-making process can be viewed as a logical, timed-based, systematic process with the aim of choosing an alternative from several alternatives available, and many of the factors that affect the decision-making process stem from the national culture that governs a particular country with patterns, customs, and traditions (Okonedo, 2018). Individual factors, such as personality characteristics and psychological behaviours that distinguish individuals from each other based on their experience or level of qualification (Okonedo, 2018;Uzonwanne, 2016).…”
Section: Prescribing Decisions Of Physiciansmentioning
confidence: 99%